2020
DOI: 10.1186/s12905-020-01142-y
|View full text |Cite
|
Sign up to set email alerts
|

Actions taken by female sex workers (FSWs) after condom failure in semi urban Blantyre, Malawi

Abstract: Background Little is known about actions taken by female sex workers (FSWs) after male condom failure during male–female sexual intercourse. The objective of this study was to investigate the actions taken by FSWs after condom failure among FSWs in semi-urban, Blantyre in Malawi. Methods A cross sectional, qualitative study was conducted among FSWs in Blantyre, Malawi between May and July 2019. Snowballing technique was used to recruit study partic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 39 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…Fourteen of the studies were conducted in Kenya [ 10 23 ], eight in South Africa [ 13 , 14 , 24 29 ], eight in Uganda [ 30 37 ], six in Mozambique [ 13 , 14 , 38 40 ], five in Tanzania [ 41 – 45 ], three in Eswatini [ 46 48 ] and in Malawi [ 49 51 ], two in Ethiopia [ 52 , 53 ], in Zambia [ 54 , 55 ], and in Zimbabwe [ 56 , 57 ] and one each in Democratic Republic of Congo [ 58 ], Lesotho [ 59 ], Rwanda [ 60 ], and online (Australia, Brazil, El Salvador, France, Kenya, Malawi, Russia, South Korea, Spain, Tanzania, the United States of America, and Zimbabwe) [ 56 ]. Thus, knowledge production concerning WSS in relation to non-barrier contraception, pregnancy and abortion is dominated by studies conducted in Kenya.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fourteen of the studies were conducted in Kenya [ 10 23 ], eight in South Africa [ 13 , 14 , 24 29 ], eight in Uganda [ 30 37 ], six in Mozambique [ 13 , 14 , 38 40 ], five in Tanzania [ 41 – 45 ], three in Eswatini [ 46 48 ] and in Malawi [ 49 51 ], two in Ethiopia [ 52 , 53 ], in Zambia [ 54 , 55 ], and in Zimbabwe [ 56 , 57 ] and one each in Democratic Republic of Congo [ 58 ], Lesotho [ 59 ], Rwanda [ 60 ], and online (Australia, Brazil, El Salvador, France, Kenya, Malawi, Russia, South Korea, Spain, Tanzania, the United States of America, and Zimbabwe) [ 56 ]. Thus, knowledge production concerning WSS in relation to non-barrier contraception, pregnancy and abortion is dominated by studies conducted in Kenya.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore list all found (noting that some may not apply in certain areas, while others may apply but were not included in the study). Variables include: personal factors – fear of side effects [ 10 , 51 ]. desire for (more) children [ 11 ], being nulliparous [ 46 ], history of incarceration or arrest [ 55 ], intoxication [ 42 ], and being older than 35 [ 31 ]; interpersonal factors—male partners’ or clients’ disapproval [ 10 ], physical or sexual abuse [9, 16], having a steady partner [ 51 ]; and systemic issues—poor clinic access [ 10 , 42 ], negative healthcare provider attitudes [ 10 ], and condom availability at work [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, firstly, behavioral interventions such as the appropriate and consistent use of male or female condoms have been shown to reduce HIV transmission and decline HIV incidence rates across the world [13, 14, 15 16]. However, concerns have been raised that, sometimes condoms may not be used for several reasons, such as in rape cases, personal choice, or condom breakage [17,18,19]. In such situations, the probability of HIV transmission may be reduced if the FSW is on PrEP.…”
Section: Introductionmentioning
confidence: 99%
“…The use of PrEP among FSW would be a game changer as they can control its use by taking it before they have contact with their clients. Several studies have reported that FSWs who had a condom burst or been engaged in unprotected sexual exposure with clients with unknown HIV status didn't use post-exposure prophylaxis (PEP) and were not on PrEP to prevent HIV infection [17,18,19].…”
Section: Introductionmentioning
confidence: 99%